2021
DOI: 10.3389/fphar.2021.632107
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Associated Acute Kidney Injury: A Longitudinal Study in China

Abstract: Background: Vancomycin-associated acute kidney injury (VA-AKI) is a recognizable condition with known risk factors. However, the use of vancomycin in clinical practices in China is distinct from other countries. We conducted this longitudinal study to show the characteristics of VA-AKI and how to manage it in clinical practice.Patients and Methods: We included patients admitted to hospital, who received vancomycin therapy between January 1, 2016 and June 2019. VA-AKI was defined as a patient having developed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of vancomycin and piperacillin-tazobactam is among the most often prescribed antibiotic therapies in the hospital setting [47]. Previous clinical studies found that piperacillin-tazobactam carries a significantly higher risk of AKI than other comparator antibiotics when concurrently prescribed with vancomycin [16]. Although conflicting results exist [48,49], similar findings were reported in some review work, a meta-analysis [50], and a network meta-analysis [51].…”
Section: Concomitant Administration With Piperacillin-tazobactammentioning
confidence: 70%
“…The reported incidence of VA-AKI ranges from 5% to 43% according to various clinical settings and AKI definitions. More recently, many investigators recommend diagnosing VA-AKI using existing AKI criteria, such as RIFLE, AKIN, and KDIGO criteria [11,13,16]. Nevertheless, the coexistence of infections and other risk factors for AKI in most reported cases makes it hard to evaluate the true incidence rate of VA-AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous cross‐sectional surveys of vancomycin‐associated AKI revealed that the main management barriers to reducing AKI were lack of standardization of vancomycin TDM and lack of SCr measurements for the diagnosis of AKI 45–47 . For patients who were recommended to monitor vancomycin trough concentration, the actual monitoring rate was only 26.3–32.5% 45–47 . Only 8.2–21.5% patients were monitored initially before the fourth or fifth vancomycin administration 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…53 However, the SCr of patients treated with vancomycin have not been adequately monitored. [45][46][47] Appropriate and timely monitoring of renal function contributes to the early and adequate diagnosis of AKI, the timely treatment of AKI, and ultimately improves the prognosis of patients. 50 In this meta-analysis, only 2 of the 34 studies reported the date of SCr monitoring, 11,18 which may imply that both pharmacists and physicians were not paying enough attention to the monitoring of renal function.…”
Section: Therapeutic Drug Monitoring Managementmentioning
confidence: 99%